2020
DOI: 10.1051/meca/2019084
|View full text |Cite
|
Sign up to set email alerts
|

Temperature rise characteristics of the valve-controlled adjustable damping shock absorber

Abstract: The thermodynamic study of the valve-controlled adjustable damping shock absorber is conducted in order to solve the problem of oil leakage caused by excessive temperature rise of shock absorber. In this paper, the temperature rise of the valve-controlled adjustable damping shock absorber is analyzed from the perspective of energy conservation. Combined with the theory of fluid mechanics, the damping heat model is established, and the heat dissipation model of the shock absorber is established based on heat co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…During the operation of the shock absorber, the suction valve 4 and the intake valve 9 can be opened only with a small oil pressure, while the rebound valve 2 and the compression valve 5 can be opened when the fluid reaches a certain pressure [24][25]. The opening of the rebound valve 2 and the compression valve 5 is directly related to the vibration velocity of the piston and determines the damping force of the shock absorber [2,[26][27]. Under different vibration velocities of the piston, the structural parameters of the shock absorber valve systems have different effects on the damping force.…”
Section: Damping Characteristics Of the Shock Absorbermentioning
confidence: 99%
See 1 more Smart Citation
“…During the operation of the shock absorber, the suction valve 4 and the intake valve 9 can be opened only with a small oil pressure, while the rebound valve 2 and the compression valve 5 can be opened when the fluid reaches a certain pressure [24][25]. The opening of the rebound valve 2 and the compression valve 5 is directly related to the vibration velocity of the piston and determines the damping force of the shock absorber [2,[26][27]. Under different vibration velocities of the piston, the structural parameters of the shock absorber valve systems have different effects on the damping force.…”
Section: Damping Characteristics Of the Shock Absorbermentioning
confidence: 99%
“…The shock absorber is used to absorb the vibration from the road, and its performance directly affects the ride comfort and handling stability of the vehicle [1][2][3][4][5]. The vibration absorption performance of a shock absorber is determined by its damping characteristics, which is closely related to the deformation of the valve slice in the shock absorber valve system [6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In previous scientific research, shock absorber tests results could be found that take into account temperature [5,10,14,18] and their impact on the driving comfort of the user [13]. Studies of the shock absorbers filled with numerous types of fluids were also presented in [12], where the authors presented their heating characteristics during operation with a constant amplitude and frequency.…”
Section: Highlights Abstractmentioning
confidence: 99%
“…Many researchers from different countries have carried out research into the characteristics of hydraulic shock absorbers. Some of them [4], for example, have studied the effect of low temperatures and others [5][6][7][8][9][10][11][12][13][14][15][16][17][18], in turn, of high temperatures on their damping characteristics. The effect of low temperatures and technical conditions on the characteristics of a hydraulic damper was studied by Z. Hryciow [19].…”
Section: Introductionmentioning
confidence: 99%